Symptoms of PTSD Associated With Painful and Nonpainful Vicarious Reactivity Following Amputation. Issue 4 (4th August 2015) - Giummarra, Melita J.; Fitzgibbon, Bernadette M.; Tsao, Jack W.; Gibson, Stephen J.; Rich, Anina N.; Georgiou‐Karistianis, Nellie; Chou, Michael; Bradshaw, John L.; Alphonso, Aimee L.; Tung, Monica L.; Drastal, Carol A.; Hanling, Steven; et al.
<x xml:space="preserve">Abstract</x> Although the experience of vicarious sensations when observing another in pain have been described postamputation, the underlying mechanisms are unknown. We investigated whether vicarious sensations are related to posttraumatic stress disorder (PTSD) symptoms and chronic pain. In Study 1, 236 amputees completed questionnaires about phantom limb phenomena and vicarious sensations to both innocuous and painful sensory experiences of others. There was a 10.2% incidence of vicarious sensations, which was significantly more prevalent in amputees reporting PTSD‐like experiences, particularly increased arousal and reexperiencing the event that led to amputation (φ = .16). In Study 2, 63 amputees completed the Empathy for Pain Scale and PTSD Checklist‐Civilian Version. Cluster analyses revealed 3 groups: 1 group did not experience vicarious pain or PTSD symptoms, and 2 groups were vicarious pain responders, but only 1 had increased PTSD symptoms. Only the latter group showed increased chronic pain severity compared with the nonresponder group (p = .025) with a moderate effect size (r = .35). The findings from both studies implicated an overlap, but also divergence, between PTSD symptoms and vicarious pain reactivity postamputation. Maladaptive mechanisms implicated in severe chronic pain and physical reactivity posttrauma may increase the incidence of vicarious reactivity to the pain of others.